IMPACT OF ORGANIZATIONAL CULTURE ON THE IMPLEMENTATION OF MANAGEMENT ACCOUNTING SYSTEMS IN INDONESIAN SMES - Aris Setia Noor; Parawiyati Parawiyati; Diana Zuhroh (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study explores the influence of organizational culture dimensions on Management Accounting System (SAM) implementation by considering the role of regulation and external support as mediators. Using multiple regression analysis, the results show that Innovative Culture and Collective Culture have a significant positive influence on SAM implementation, while Hierarchical Culture exerts a negative influence. Regulation and external support also have a significant positive effect on SAM and serve as mediators in the relationship between Innovative Culture and Collective Culture with SAM implementation. These findings highlight the importance of creating a culture that supports innovation and cooperation, as well as utilizing external support to enhance the success of SAM implementation. This research makes an important contribution to organizational culture theory and system implementation practice, by demonstrating that external regulation and organizational culture interact in influencing system implementation outcomes.